USING INTERACTIVE METHODS IN IMPROVING SPELLING LITERACY (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article shows the features of the use of innovative technologies used in the study of speech sounds in literacy classes in primary grades.